Design of the Vertical Roundness Tester Machine Using the AHP Method (Analytical Hierarchy Process) Through the DFM Approach (Design for Manufacturing) - Agus Reforiandi; Dodi Sofyan Arief (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2021)
The Roundness Tester Machine is a tool used to take measurements that are shown to check the Roundness of an object or to find out whether an object is really round or not when viewed carefully using a measuring instrument. DFM (Design for Manufacturing) is a method for reducing production costs by estimating production costs through reducing component costs, assembly costs, and other production supporting costs based on design submission data without reducing product quality. AHP (Analytical Hierarchy Process) method was chosen as a method to determine the optimal Vertical Roundness Tester Machine design based on a questionnaire given to the expert, to choose the best alternative decision. The questionnaire was created to get priority customer needs which was then used for the initial design. The next stage is selecting the optimal design using AHP which involves experts based on indicators of a product. The highest indicator value obtained on the Vertical Roundness Tester Machine is the accuracy indicator with a value of 48.52%. Then in choosing the optimal design in the DFM analysis, namely in alternative 3, where alternative 3 is the design with the lowest cost so as to minimize the cost of making a Vertical Roundness Tester Machine. The manufacturing cost for alternative design 3 is Rp. 4,173,000.